An efficient catalyst-free Mukaiyama-aldol reaction of fluorinated enol silyl ethers with tryptanthrin1. Issue 33 (7th September 2015) - Liao, Fu-Min; Liu, Yun-Lin; Yu, Jin-Sheng; Zhou, Feng; Zhou, Jian
<x xml:space="preserve">Abstract</x> We report an efficient Mukaiyama-aldol reaction of tryptanthrin with fluorinated enol silyl ethers, which is carried out in methanol without the use of any catalyst. This represents the first modification of tryptanthrin by a fluoroalkyl group, which is applied to the total synthesis of the difluoro analogues of the natural product Phaitanthrin B.